The Effect of Case Method and Primary Nursing Method on the Social Dimension in Quality of Patient Care - Simin Sharafi; Hamid Chamanzari; Zohre Pouresmail; Mohammad Rajabpour; Ali Bazzi (Guilan University of Medical Sciences, 2018)
Introduction: The quality of care in patient s view lacks the optimal and desired level in hospital wards with respect to psychosocial dimension. Moreover, there is a direct relationship between the methods of the division labor of nurses and the quality of patient care. Objective: This study aimed to compare the primary nursing method and case method on the psychosocial dimension of the quality of patient care in Coronary Care Units (CCU). Materials and Methods: This is a experimental study conducted on 60 patients in two groups at 4 CCUs of Educational Centers in Mashhad City, Iran in 2014. After performing these two methods, the quality of patient care with respect to psychosocial dimensions were assessed by the interview method using the quality of patient care questionnaire. Finally, the results were analyzed using the Independent t test, Mann-Whitney and Chi-square tests. Results: The mean age of patients was 56.4±13.7 years and the mean age of nurses was 37.4±4.4 years. The mean score of individual psychosocial dimension was 41.7±7.1 for the primary nursing method group and 27.6±8.9 for the case method group. Also the mean score of group psychosocial dimension for the quality of care in primary nursing method 17.3±5.7 and case method 12.3±7.6 groups using Independent t test showed a significant difference between the two groups, i.e. the quality of both individual and group psychosocial dimensions in the primary group were significantly higher (P=0.0001). Conclusion: It seems that the implementation of primary nursing method can partly improve the quality of care in individual and group psychosocial dimensions.